(untitled) (JONAH : Journal of Nursing and Homecare, 2022)
Elderly is someone who has entered the age of 60 years and over. The disease that often occurs in the elderly is Gout Arthritis. Gout Arthritis is a metabolic disease associated with a high-purine diet and alcoholic beverages. One of the non-pharmacological treatments for patients with Gout Arthritis is a warm compress. Red ginger has an anti-inflammatory effect to improve blood circulation and to relieve pain. The prevalence of Gout Arthritis in Riau is 6.8% and Kuantan Singingi Regency ranks fourth. UPTD Sentajo Health Center is one of the UPTD in Kuantan Singingi with the number of patients with Gout Arthritis as many as 361 people. The purpose of this study was to determine the effectiveness of giving grated red ginger warm compresses to reduce the Gout Arthritis pain scale in the elderly. This Methods research is a quantitative researche with a Quasi Experimental design. Determination of the sample is done by using purposive sampling technique. The sample consisted of 20 respondents, namely 10 respondents as the control group and 10 respondents as the experimental group. Data analysis consisted of univariate and bivariate using paired T test with non-parametric Wilcoxon test. The Results There was a significant difference in the average intensity of gout arthritis pain before and after being given a warm compress of grated red ginger (p = 0.008). In the control group there was also a significant difference in the average pain intensity before and after being given warm water compresses (p = 0.024)